Coral Reefs in the Gulf of Mexico Large Marine Ecosystem: Conservation Status, Challenges, and Opportunities - Gil-Agudelo, Diego L.; Cintra-Buenrostro, Carlos E.; Brenner, Jorge; González-Díaz, Patricia; Kiene, William; Lustic, Caitlin; Pérez-España, Horacio (Frontiers in Marine Science, 2020)
The importance of coral reefs (CR) within marine ecosystems has become widely recognized. Although shallow CR are not as abundant in the Gulf of Mexico (GoM) as in other areas such as the Caribbean, their uniqueness, singularity, isolation and conservation status make their conservation highly important. Corals and CR, both shallow and deep, are more widely distributed throughout the GoM than previously thought, providing new venues of research but also new challenges for their sustainable management. They are widely present in the three countries circumscribing the GoM (Cuba, Mexico and the United States). Corals are also distributed throughout different depths, from the keys of corals of Florida and Cuba, to the mesophotic reefs in Flower Garden Banks, Pulley Ridge and submerged banks in the southern GoM; additional coral presence occurs even beyond mesophotic depths (~30-150 m). Like reefs around the world, they are subject to an increased threat from anthropogenic causes, including overfishing, pollution and climate change. But there is also hope. Some reefs in the area, such as those in Flower Garden Banks National Marine Sanctuary are probably the best-preserved reefs in the region, with coral cover greater than 50%, which is unusual in the Wider Caribbean. Others are experiencing new protections through the work of government and local communities. The objectives of this manuscript are to summarize the overall status of corals and CR in the GoM, analyze some of the current and future threats, and explore opportunities for their conservation in the region. Aside from the above mentioned anthropogenic threats bleaching, coral diseases and hurricanes have been identified as main contributors for CR declines not only in the GoM but abroad; some nowadays present but likely to increase threats are invasion by alien species or by Sargassum spp. Among some of the opportunities identified are to capitalize on existing and emerging multilateral agreements and initiatives (e.g., GoM Large Marine Ecosystem, trinational sanctuaries agreement); increase financial support for conservation through international initiatives and the private sector; and a need to comprehend the inherent interconnection among corals, CR and deeper bank ecosystems as they do not function in isolation.